Factors Risk Incident Primary Hypertension in Communities in Working Areas Public Health Center Medan Marelan Year 2022 - Zaim Anshari (PT Inovasi Pratama Internasional, 2022)
High blood pressure or hypertension (Hypertension) is a condition where a person experiences an increase in blood pressure above normal as indicated by systolic numbers and diastolic numbers on blood pressure checks using blood pressure gauges either in the form of mercury cuffs (sphygmomanometers) or instruments other digital. This study is a descriptive study with a cross-sectional approach (cross-sectional study), where this study aims to determine the description of risk factors for Primary Hypertension in the working area. Age distribution showed that as many as 47 respondents (50%) patients with primary hypertension were in the middle age category (45-59 years). Based on the results of data analysis the most dominant sex was female with a total of 61 (64.9%), Based on the analysis of family history data, the more dominant family history with a history of hypertension was 48 (51.1%). Based on the analysis of salt consumption data, it was found that hypertensive patients who frequently consumed salt amounted to 80 (85.1%). consumption of fatty foods found that hypertensive patients who often consume fatty foods amounted to 59 (62.8%), Based on the results of data analysis smoking history found that hypertensive patients who smoke amounted to 22 (23.4%), Based on the results of physical activity data analysis found that patients who enough physical activity totaling 54 (23.4%), Based on the results of the analysis of the status data g izi found that patients with BMI ≥30 totaled 19 (20.2%), while hypertensive patients with BMI <30 totaled 75 (79.8%)